The smoke emission properties of selected elements of passenger car interior design - Zubek Łukasz (E3S Web of Conferences, 2018)
The paper presents the results of tests for smoke optical density conducted on five various elements of car interior design. The tested samples were taken from the dashboard, ceiling lining, floor lining, seats and side door upholstery. A smoke density chamber was used to measure the propensity of the materials to generate smoke after being exposed to a heat source. The specific optical density, as a function of time, was determined for each material. There were two burning conditions simulated: radiant heating in the absence of ignition, and flaming combustion in the presence of supporting radiation. The highest values for specific optical density were measured for the side door upholstery and driver’s dashboard. The tests results were compared with international optical smoke density requirements for the interior design of ships and trains.